1993
DOI: 10.1017/s0022215100125241
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary plasmacytoma of the larynx

Abstract: A case of IgD myeloma in a 54-year-old male with a long-standing history of extramedullary plasmacytoma involving the larynx is reported.The patient was treated with radiation therapy and laryngectomy. Twelve years later, he complained of nasal bleeding. On examination he was found to have large masses in the left nasal cavity and in the left supraclavicular region. Histological examination of both lesions showed plasmacytoma. Serum immunoglobulin studies revealed an IgD monoclonal spike of the lambda type. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…In a study on 25 cases, reported by Sunsnerwala et al, the median survival rate was 68 months for EMP [ 19 ] and 14.5 for MM arising from EMP [ 18 ]. A long follow-up is advisable as EMP may have long time intervals between relapse and progression to MM, even as long as 10 years [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on 25 cases, reported by Sunsnerwala et al, the median survival rate was 68 months for EMP [ 19 ] and 14.5 for MM arising from EMP [ 18 ]. A long follow-up is advisable as EMP may have long time intervals between relapse and progression to MM, even as long as 10 years [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact EMP may evolve to MM many months or years later after diagnosis [14,15]. When a plasma cell tumor involving the larynx is diagnosed the next step is to exclude systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Suele presentarse durante la 6ª-7ª déca-da. En el 90% de los casos se localizan en cabeza y cuello (fosa nasal, seno maxilar y nasofaringe) 4 , otras localizaciones son pulmón (5%), ganglios linfáticos (5%), tracto gastrointestinal y piel. Típica-mente en pulmón se presenta como nódulo pulmonar solitario, menos frecuente como consolidación pulmonar o en forma de infiltrados difusos 5 .…”
Section: Discussionunclassified
“…Por último mencionar que es imprescindible un buen seguimiento del paciente tras el tratamiento ya que no son infrecuentes las recidivas tanto locales, que pueden anunciar la diseminación tumoral 4 , como sistémicas (35-50%), sobretodo de vías aéreas bajas, pulmón, tubo digestivo y piel que metastarizan más rápido y presentan peor pronóstico así como la progresión a mieloma múltiple (20-30%).…”
Section: Discussionunclassified